AN ANALYSIS OF CLASSROOM INTERACTION ON EFL STUDENTS - Ni Made Nurmayang Sari (Inspiring: English Education Journal, 2022)
This study aims to determine the nature of classroom interaction carried out by the pre-service teacher and class VII students at SMP Negeri 2 Tejakula. The theories used are Malamah-Thomas (1987) and the IRF classroom pattern. The method used is qualitative with case studies. The instrument in this study was a video recording of the learning process, which was analyzed using naturalistic observations and document analysis. Based on the research, it was found that the teacher and students did several types of classroom interaction, such as teacher speaking to the whole class, teacher speaking to an individual, teacher speaking to a group of students, student speaking to teacher, student speaking to another student, student speaking to group members, and student speaking to the whole class. Based on the IRF classroom pattern, the most dominant pattern is IRF (complete pattern).